Language Teaching and its Articulation with Texts and Discourses: Toward a Multilevel Didactics (Papeles, 2026)
Introduction: This paper analyzes methodological inadequacies in language teaching and proposes to outline multilevel didactic models for articulating grammar, texts, and discourse in initial teacher training of Language and Literature Teaching. Methodology: The research adopts a qualitative, situated and relational perspective. It analyses curriculum documents and ethnographic records of classroom scenes observed in secondary schools, drawing on socio-anthropological contributions, language teaching with an ethnographic perspective, and socio-discursive interactionism, to examine teaching work and the teaching of the language system. Results and discussion: The analysis of curricular documents shows a progressive mainstreaming of reflection on language, subordinated to reading and writing practices and formulated in procedural terms. In the classes observed, language emerges as a teaching object in a limited and episodic way, mainly through semantic dimensions of subordinate units in articulation with the discursive purposes of the genres worked on. However, significant constraints are identified in the systematization of grammatical knowledge, especially morphological and syntactic knowledge. The discussion highlights tensions in the genre-based teaching sequence model and highlights the need for multilevel teaching sequences that allow explicit and progressive teaching of the language system. Conclusions: The study proposes that language teaching is focused on texts, which require teaching sequences in which the various linguistic levels are accessed with greater precision.
Keywords: Secondary education; language; mother tongue instruction; educational policy; secondary teacher training